A importância da improvisação cênica no desenvolvimento expressivo de alunos da educação especial: uma experiência - Paula, John Karllus (2016)
This study, by means of observations of experiences and theatrical presentations, aims to understand the relationship between theater and Special Education, allowing an emotional, cognitive and motor development and the appreciation of handicapped people, as individuals with creative potential. Methodologically, ludic activities, spontaneous theatrical exercises, as well as essays, supervised by the author-teacher, were performed and proposed with 05 students, so that the students could experience, through art, theater, spontaneity and their expression capability in the world. In the context of ludic stimulation, the story of Charles Perrault, Cinderella, was selected for interpretation and improvisation. The choosing of characters, as well as the marking of the scenes was ruled by the freedom and spontaneity of the students, which allowed improvisation to happen during presentations. Presentations were performed at two schools of Primary Education on the Triângulo Mineiro, in a Region Seminar and in a Regional Theatrical Showcase (Mostra de Teatro Regional). Generally speaking, it was possible to notice, through the speeches of the students, that the theatrical presentations provided to the people involved: a) an improvement on self-confidence and autonomy; b) stronger involvement with the theatrical proposal; c) stronger communication capability; d) bigger popularity; e) more easiness in the ways of connecting to other people; e f) the meaning of the disability as a characteristic and not as a condition that defines the person. Therefore, I believe this proposition has transformed the lives of the 05 students whom participated in the project, considering they were seen as useless, and, after the project, they became a reference and inspiration for other students who have some kind of disability.